The licensing of shops - Meredith, James C. (Statistical and Social Inquiry Society of Ireland, 1927)
The extension and multiplication of licensing provisions is a natural, and perhaps inevitable, outcome of the development and growing complexity of civilization and social organization. This tendency is viewed with feelings of profound suspicion, and sometimes violent hatred, by persons of a certain temperament or outlook?by those, namely, of a predominantly individualistic turn of mind?those who prize individual freedom beyond anything else. With others, however, the idea- of the restriction of individual freedom is mainly associated with the idea of schemes for the improvement of social conditions, which, as at present, are regarded by them as intolerably bad, and to those of such a socialistic turn of mind a policy of control has no terrors. With some this socialistic impulse is so strongly developed that they seem almost ready to welcome State control as if it were something good inherently and on its own account. As this is not merely a Statistical but also a Social Inquiry Society, it cannot be beyond the scope of a paper proper to be submitted to the Society to deal to some extent with the general bearings of the problem of restrictions upon and the control of a freedom that is at present practically unfettered, which restriction and control are implied by any proposal as to licensing shops, and also to deal with the theory and experienced effects of licensing provisions so far as may seem instructive with regard to the particular question under consideration.
Read Thursday, 12th May, 1927
Keywords: Shop licencing; Retail regulation; 314.15